Kajian Literatur: Berhubungankah mikrobiota saluran cerna dengan stunting pada anak balita? Kajian Literatur: Berhubungankah Mikrobiota Saluran Cerna dengan Stunting pada Anak Balita? - Betty Yosephin Simanjuntak; Rahma Annisa; Arie Ikhwan Saputra (Universitas Airlangga, 2022)
Background: Stunting, one of the malnutrition that started since in pregnant until 2 first life's years and made worse by repeated infection disease. Objectives: This study aims to identify the correlation between the presence of gut microbiota and stunting. Discusion: This study explored article Pubmed database, Science Direct, Sage Journal, Springer Link, through keywords “stunting, gut microbiota, under 5 years”. Furthermore, the studies found are 5 open access articles, and were filtered since 2016 until 2021. The guts microbiota may contribute to stunting in children. Gastrointestinal infection has spesific mechanism that causing postnatal stunting. Immaturity and deficiency of non-pathogenic microbiota in the gut are the main causes. Decreased gastrointestinal microbiota diversity in children who suffer diarrhea and stunting. Conclusions: composition change of the gut bacteria of children have been associated with an increase in the number of gastrointestinal infections resulting in chronic growth disorders.